Fast track to success : risk management - Baxter, Keith, 1959- (Fast track to success., 2010)
A complete resource to show you how to get ahead as a manager faster by gaining a clearer understanding of risk management, this title shows you how to quickly assess your current state of risk management effectiveness using a simple framework.